2018
DOI: 10.17700/jai.2018.9.1.431
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of logging forest residues as an energy source

Abstract: Forest residue extraction levels in Greece are currently very low, but logging residues have the potential to be an important component of the wood energy supply chain. Forests are a major supplier of renewable energy. Exploring the possibilities of utilizing the biomass of logging residues for energy requires analysis and knowledge of its properties. In this research work the properties (ash, volatiles, fixed carbon, carbon, hydrogen, oxygen, nitrogen and calorific value) of the various constituents of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…36 The nitrogen content of oak wood (cork is a type of oak) varies between around 0.2-1.1%, depending on the species and the part of the tree analysed. 37 Therefore, we would expect there to be a remaining small N content in any carbon from pyrolysed wood, and this percentage will be greater in the pyrolysed carbon than in the original wood, as O and H is lost in the process. We have shown that our cork pyrolysed in N 2 contained 1.57 wt% nitrogen, 38 which is of the levels to be expected from the original wood content, and probably does not indicate any extra N doping from the pyrolysis atmosphere.…”
Section: Pyrolysis Of Corkmentioning
confidence: 99%
“…36 The nitrogen content of oak wood (cork is a type of oak) varies between around 0.2-1.1%, depending on the species and the part of the tree analysed. 37 Therefore, we would expect there to be a remaining small N content in any carbon from pyrolysed wood, and this percentage will be greater in the pyrolysed carbon than in the original wood, as O and H is lost in the process. We have shown that our cork pyrolysed in N 2 contained 1.57 wt% nitrogen, 38 which is of the levels to be expected from the original wood content, and probably does not indicate any extra N doping from the pyrolysis atmosphere.…”
Section: Pyrolysis Of Corkmentioning
confidence: 99%